Teorija Dorothy Johnson in zdravstvena nega nosečnice - Urh, Irma (Obzornik zdravstvene nege, 1998)
The article deals with the role of nursing care during antenatal period. Basedon an behavioural model, activities of a nurse intendend to help a pregnant woman and her partner from conception to birth of their child. The article deals with the process of nursing care based on the ideals of Dorothy Johnson's theory for planning and performing nursing care for a particular pregnant women.
Keywords: Behavior; human pregnancy; Methods; nosečnice; nosečnost; Nursing care; Obstetrical nursing; Pregnancy; zdravstvena nega